Correlaciones de ensayos de campo SDMT, CPT y laboratorio para caracterización de arcillas en el sector comprendido entre la calle 127 y la caro, en Bogotá (2018)
The present article aims to publicize the characterization of the clays that are included between 127th Street and La Caro, in the city of Bogotá. For this, basic laboratory tests were taken into account (soil moisture, Atterberg limits, unconfined compression and consolidation) and field tests (CPT and SDMT), with which they were evaluated for the undrained resistance parameter (Su ) the correlations proposed by Skempton, Jamiolkowski, Mesri and Itansbo, and for the OCR parameter, the correlations proposed by Stas and Kulhawy, Mayne and Mitchell were used. With the respective evaluation of the expressions raised by the mentioned authors, a comparison was made with the field results (SU, OCR), to later define the characteristic correlation equations for the soil under study. With these aforementioned correlation equations, an approximation to the SU and OCR results can be obtained, from the laboratory and field tests.